From both sides of the needle: Understanding effective interventions for facilitating non-national immunization program vaccine decision making in China - Mingzhu Jiang; Xuanxuan Yan; Weixi Jiang; Haifeng Ma; Sijuan Zhou; Xiaohua Ying (Human Vaccines & Immunotherapeutics)
Vaccination decisions are influenced by various psychological and practical factors. In China, non-National Immunization Program (non-NIP) vaccines, which are voluntary and self-paid, add uncertainty and autonomy to the decision-making process. Effective communication between providers and recipients is crucial but understudied. This study aims to integrate their perspectives, identify strategies for facilitating vaccination decisions, and analyze their mechanisms. From July to December 2023, semi-structured interviews were conducted with 17 caregivers and 12 vaccination providers across five Chinese provinces. Participants shared their experiences and decision-making processes regarding non-NIP vaccines. The Behaviour Change Wheel framework guided the analysis, utilizing iterative coding and directed content analysis. Thirteen Behavior Change Techniques were identified, with feedback, monitoring, and environmental restructuring being the most common. Key intervention functions included Persuasion, Education, and Training. We further mapped how these interventions influence non-NIP vaccine decisions. Capability was enhanced through education and effective communication, providing necessary knowledge and skills. Opportunity was increased via infrastructural improvements and societal support, making vaccines more accessible and endorsed by the community. Motivation was driven by clear communication of vaccination benefits and risks, reinforced by societal norms through public health messaging. By understanding the mechanisms influencing vaccination behaviors and interacting with stakeholders, tailored strategies can be developed. Healthcare providers can enhance service accessibility and offer evidence-based guidance with reminders, monitoring, and incentives to ensure compliance. For recipients, reliable information, sustained engagement, timely communication, and motivational opportunities are essential. A multi-dimensional approach involving multiple stakeholders is crucial for promoting non-NIP vaccine uptake.